Rhythm in acting and performance embodied approaches and understandings - Morris, Eilon (London New York, NY Bloomsbury Methuen Drama, 2017)
Rhythm is often referred to as one of the key elements of performance and acting, being of central importance to both performance making and training. Yet what is meant by this term and how it is approached and applied in this context are subjects seldom discussed in detail. Addressing these, Rhythm in Acting and Performance explores the meanings, mechanisms and metaphors associated with rhythm in this field, offering an overview and analysis of the ways rhythm has been, and is embodied and understood by performers, directors, educators, playwrights, designers and scholars. From the rhythmic movements and speech of actors in ancient Greece, to Stanislavski's use of Tempo-rhythm as a tool for building a character and tapping emotions, continuing through to the use of rhythm and musicality in contemporary approaches to actor training and dramaturgy, this subject finds resonance across a broad range of performance domains. In these settings, rhythm has often been identified as an effective tool for developing the coordination and conscious awareness of individual performers, ensembles and their immediate relationship to an audience. This text examines the principles and techniques underlying these processes, focusing on key approaches adopted and developed within European and American performance practices over the last century. Interviews and case studies of individual practitioners, offer insight into the ways rhythm is approached and utilised within this field.
Includes bibliographical references and index.
Keywords: Movement (Acting); Acting -- Psychological aspects; Rhythm; Drama -- Technique